Les cadres d'une géographie touristique du Québec - Brière, Roger (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1961)
It is a well known fact that tourism is an important resource for the Province of Québec. This paper attempts to give a brief account of this geographical phenomenon as it occurs in Québec, with regards to the forms {touring, temporary out-of-town lodging, weekend commuting), attractions (physical, cultural), equipment (hotels, motels, country homes, cottages, parks, transport), and regional variations.